RASA NASIONALISME DI DAERAH PERBATASAN (STUDI PERAN STUDIO PRODUKSI RRI TERHADAP MASYARAKAT PERBATASAN DI KABUPATEN BENGKALIS TAHUN 2015) - Arie Hasmi Rachmadi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted to describe how the role of Production Studio RRI Bengkalis in keeping nationalism in the border area in Bengkalis. The purpose of this research was to see the extent to which the role of Production Studio RRI Bengkalis in keeping nationalism border communities in Bengkalis 2015.This research is a descriptive research using a qualitative approach as a tool of analysis. The research was conducted in Bengkalis. This study uses document observation and interview with key informants as an object of information that aims to achieve the goal to have the information in this study. Data used in this study are primary data and secondary data obtained through direct observation and interviews with key informants in this research.RRI Bengkalis role in keeping nationalism in the border area can be seen from the role that has been done is its role in strengthening national identity and centering margin, which is where the problem of sound quality RRI Production Studio Bengkalis not good enough to be heard by residents in the border area of Bengkalis. Supposedly Production Studio RRI Bengkalis radio is the only government can provide good sound quality for citizens in border regions may obtain information better and comfortable.Keywords : Role, Nasionalism, Border Area